Composition and antifungal activity of the essential oil of Nashia inaguensis Millsp. (Verbenaceae) cultivated in French Guiana. Issue 4 (3rd July 2016) - Scotto, Camille Inès; Burger, Pauline; Khodjet el Khil, Mehdi; Ginouves, Marine; Prevot, Ghislaine; Blanchet, Denis; Delprete, Piero G.; Fernandez, Xavier
Abstract: This study reports the chemical composition of the essential oil of Nashia inaguensis Millsp. organically cultivated in French Guiana. This essential oil was examined by a combination of GC/FID and GC-MS techniques. A total of thirty-one components accounting for 97% of the total GC/FID chromatogram were identified. The most abundant ones were carvacrol (23.1%), p -cymene (18.7%), γ-terpinene (14.6%), thymol methyl ether (10.3%), thymol (8.3%), trans -β-caryophyllene (8.0%) and myrcene (2.3%). The essential oil of N.inaguensis was tested for the first time for antifungal and antiparasitic activities against strains of several Candida spp. and Leishmania guyanensis respectively: the strong antimicrobial activity of this essential oil was confirmed in vitro by the definition of MIC values ranging from 125 μg/mL to 500 μg/mL according to the Candida species tested, while the anti- Leishmania activity assessed by the definition of an IC50 value seem negligible.